Characterizing Adult Cervical Deformity and Disability Based on Existing Cervical and Adult Deformity Classification Schemes at Presentation and Following Correction. Issue 2 (30th May 2017) - Passias, Peter G; Jalai, Cyrus M; Smith, Justin S; Lafage, Virginie; Diebo, Bassel G; Protopsaltis, Themistocles; Poorman, Gregory; Ramchandran, Subaraman; Bess, Shay; Shaffrey, Christopher I; Ames, Christopher P; Schwab, Frank; et al.
Abstract: BACKGROUND: Adult cervical deformity (ACD) classifications have not been implemented in a prospective ACD population and in conjunction with adult spinal deformity (ASD) classifications. OBJECTIVE: To characterize cervical deformity type and malalignment with 2 classifications (Ames-ACD and Schwab-ASD). METHODS: Retrospective review of a prospective multicenter ACD database. Inclusion: patients ≥18 yr with pre- and postoperative radiographs. Patients were classified with Ames-ACD and Schwab-ASD schemes. Ames-ACD descriptors (C = cervical, CT = cervicothoracic, T = thoracic, S = coronal, CVJ = craniovertebral) and alignment modifiers (cervical sagittal vertical axis [cSVA], T1 slope minus cervical lordosis [TS-CL], modified Japanese Ortphopaedic Association [mJOA] score, horizontal gaze) were assigned. Schwab-ASD curve type stratification and modifier grades were also designated. Deformity and alignment group distributions were compared with Pearson χ 2 /ANOVA. RESULTS: Ames-ACD descriptors in 84 patients: C = 49 (58.3%), CT = 20 (23.8%), T = 9 (10.7%), S = 6 (7.1%). cSVA modifier grades differed in C, CT, and T deformities ( P < .019). In C, TS-CL grade prevalence differed ( P = .031). Among Ames-ACD modifiers, high (1+2) cSVA grades differed across deformities (C = 47.7%, CT = 89.5%, T = 77.8%, S = 50.0%, P = .013). Schwab-ASD curve type and presence (n = 74, T = 2, L = 6, D = 2) differed significantly in S deformities ( P < .001). Higher Schwab-ASD pelvic incidence minus lumbar lordosis grades were less likely in Ames-ACD CT deformities ( P = .027). Higher pelvic tilt grades were greater in high (1+2) cSVA (71.4% vs 36.0%, P = .015) and high (2+3) mJOA (24.0% vs 38.1%, P = .021) scores. Postoperatively, C and CT deformities had a trend toward lower cSVA grades, but only C deformities differed in TS-CL grade prevalence (0 = 31.3%, 1 = 12.2%, 2 = 56.1%, P = .007). CONCLUSION: Cervical deformities displayed higher TS-CL grades and different cSVA grade distributions. Preoperative associations with global alignment modifiers and Ames-ACD descriptors were observed, though only cervical modifiers showed postoperative differences.